Upaya Perlindungan Hukum Terhadap Korban Kekerasan dalam Rumah Tangga Khususnya Perempuan dalam Perspektif HAM - Ridho Tri Septiawan; Indah Satria (Deposisi: Jurnal Publikasi Ilmu Hukum, 2024)
Human rights are inherent to the essence and existence of humans as creatures of God Almighty, and they are gifts that must be respected, upheld, and protected by the state, law, government, and every individual for the dignity and protection of human beings. Domestic violence (KDRT) is a violation of human rights, a crime against human dignity, and a form of discrimination that must be eliminated.The focus is on the legal protection efforts for women victims of domestic violence and the prevention and mitigation efforts against violence towards women. In conclusion, to improve this situation, integrating restitution into the criminal justice system is a solution to be considered. Therefore, while the PKDRT marks a significant step in legal protection for victims of domestic violence, integrating restitution and increasing awareness and commitment from all involved parties are crucial to ensuring better protection and justice for victims of domestic violence in Indonesia. Thus, to enhance the effectiveness of handling violence against women, good coordination among various institutions and disciplines is needed, along with strong commitment from society, law enforcement agencies, and the government to take necessary actions to create a safe and just environment for women. Recommendations for discussion include legal education and awareness, integrated protection, strengthening of medical evidence, socialization and funding, effective criminal prioritization, and restitution as an alternative. The formation of an integrated committee, strengthening gender-sensitive legal systems, education and attitude change in society, establishment of crisis centers or shelters, firm repressive actions, and integration of anti-violence norms are also suggested.